The blockchain technology and attacks on it (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Now a day’s blockchain technology has become popular because of its decentralised, peer to peer, immutable and distributed nature. It allows us to perform transactions, and store these transactions in an immutable way. It’s a kind of database in which the total data is stored in form of blocks. However due to its decentralised nature there are many challenges like scalability and security attacks. So various researchers have started their research activities in this direction. In this paper we have described the different characteristics, issues, challenges, and consensus mechanisms of blockchain. Furthermore, we have identified a number of security attacks and elaborated them with detailed discussions. There are mainly seven types of attacks identified, (i) 51% attack, (ii) distributed denial of service attack (DDoS), (iii) selfish mining attack, (iv) eclipse attack, (v) double spending attack, (vi) sybil attack and (vii) phishing attack.